The Use of Barriers to Limit the Spread of Aquatic Invasive Animal Species: A Global Review - Jones, Peter E.; Tummers, Jeroen S.; Galib, Shams M.; Woodford, Darragh J.; Hume, John B.; Silva, Luiz G. M.; Braga, Raul R.; Garcia de Leaniz, Carlos; Vitule, Jean R. S.; Herder, Jelger E.; Lucas, Martyn C. (Frontiers in Ecology and Evolution, 2021)
Aquatic invasive species (AIS) are one of the principal threats to freshwater biodiversity. Exclusion barriers are increasingly being used as a management strategy to control the spread of AIS. However, exclusion barriers can also impact native organisms and their effectiveness is likely to be context dependent. We conducted a quantitative literature review to evaluate the use of barriers to control animal AIS in freshwater ecosystems worldwide. The quantitative aspect of the review was supplemented by case studies that describe some of the challenges, successes, and opportunities for the use of the use of AIS exclusion barriers globally. Barriers have been used since the 1950s to control the spread of AIS, but effort has been increasing since 2005 (80% of studies) and an increasingly diverse range of AIS taxa are now targeted in a wide range of habitat types. The global use of AIS barriers has been concentrated in North America (74% of studies), Australasia (11%), and Europe (10%). Physical barriers (e.g. weirs, exclusion screens and velocity barriers) have been most widely used (47%), followed by electric (27%) and chemical barriers (12%). Fish were the most targeted taxa (86%), followed by crustaceans (10%), molluscs (3%) and amphibians (1%). Most studies have been moderately successful in limiting the passage of AIS, with 86% of the barriers tested deterring >70% of individuals. However, only 25% of studies evaluated barrier impacts on native species, and development of selective passage is still in its infancy. Most studies have been too short (47% <1 year, 87% <5years) to detect ecological impacts or have failed to use robust before-after-control-impact (BACI) study designs (only 5%). Hence, more effective monitoring is required to assess the long-term effectiveness of exclusion barriers as an AIS management tool. Our global case studies highlight the pressing need for AIS control in many ecoregions, and exclusion barriers have the potential to become an effective tool in some situations. However, the design and operation of exclusion barriers must be refined to deliver selective passage of native fauna, and exclusion barriers should only be used sparingly as part of a wider integrated management strategy.